The process of actively building a model for a randomization test – insights into learners’ modeling activities based on a case study - Podworny, Susanne; Biehler, Rolf (Mathematical Thinking and Learning)
Keywords: Developmental and Educational Psychology; Education; General Mathematics

A first introduction to data science education in secondary schools: Teaching and learning about data exploration withCODAPusing survey data - Frischemeier, Daniel; Biehler, Rolf; Podworny, Susanne; Budde, Lea (Teaching Statistics)
Keywords: Education; Statistics and Probability

Transforming into a Platform Provider: Strategic Options for Industrial Smart Service Providers - Beverungen, Daniel; Kundisch, Dennis; Wünderlich, Nancy (Journal of Service Management)
Purpose The purpose of this paper is to identify strategic options and challenges that arise when an industrial firm moves from providing smart service toward providing a platform. Design/methodology/approach This conceptual study takes on a multidisciplinary research perspective that integrates concepts, theories and insights from service management and marketing, information systems and platform economics. Findings The paper outlines three platform types – smart data platform, smart product platform and matching platform – as strategic options for firms that wish to evolve from smart service providers to platform providers. Research limitations/implications Investigating smart service platforms calls for launching interdisciplinary research initiatives. Promising research avenues are outlined to span boundaries that separate different research disciplines today. Practical implications Managing a successful transition from providing smart service toward providing a platform requires making significant investments in IT, platform-related capabilities and skills, as well as implement new approaches toward relationship management and brand-building. Originality/value The findings described in this paper are valuable to researchers in multiple disciplines seeking to develop and to justify theory related to platforms in industrial scenarios.
Keywords: Smart service; Platform; Interdisciplinary research; Manufacturing company; Smart service provider; Platform economics; Information systems; Multi-sided markets; Business-to-business (B2B) markets

Tax Burden on German Companies – Income Tax Burden and Administrative Costs - Fochmann, Martin; Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren

Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr

Die Studieneingangsphase. Einführung in die hochschuldidaktische Herausforderung und Entwicklung eines Kriterienrasters unter Bedingungen der Digitalisierung - Reis, Oliver (Habitusbildung in der Studieneingangsphase. Reflexionen zu einem hybriden Modell)

Transformationen des hochschuldidaktischen Dreiecks im Kontext der Digitalisierung - Reis, Oliver (Theologiestudium im digitalen Zeitalter)

Digitalisierung als Motor einer neuen (totalen) Form der instruktionsorientierten Lernsteuerung? - Reis, Oliver (Habitusbildung in der Studieneingangsphase. Reflexionen zu einem hybriden Modell)

Kraml, Martina: Anderes ist möglich. Eine theologiedidaktische Studie zu Kontingenz im Raum der Wissenschaften (Kommunikative Theologie 19). Matthias Grünewald Verlag, Ostfildern 2018. (490) - Reis, Oliver (ThPQ)

Wenn Gremien in die Jahre kommen…Wie baut man die Gremienstruktur in den Pastoralen Räumen um, damit sich Gemeinden zukunftsfähig entwickeln können? - Burke, Rebekka; Hackstedt, Carola; Hofmeister, Lisa; Kolk, Matthias; Rakowski, Jana; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Steuerung vs. Kontingenz: die Umsetzung gesetzter und realer Strukturinterventionen - Rakowski, Jana; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Zur Differenz zwischen Modell und Gemeindeentwicklung in der Praxis - Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Modellprojekt Entwicklung der ehrenamtlichen Mitverantwortung, Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen

„Wer alles hinterfragen will, muss mit dem Boden der Tatsachen anfangen“. Narrative und ihre Funktionen, Chancen und Grenzen in der religionspädagogischen Forschung - Reis, Oliver (Theo-Web)

Professionstypen in interreligiösen Lehrer*innenteams Die Wiederkehr der Materialkerygmatik in der Religionsdidaktik - Brandstetter, Bettina; Reis, Oliver; Wenig, Eva; Yagdi, Senol (Pädagogische Horizonte)

Nebeneinander ohne Konflikte. Die multiprofessionelle Struktur interreligiöser Lehrgemeinschaften - Brandstetter, Bettina; Reis, Oliver; Wenig, Eva; Yagdi, Senol (Pädagogische Horizonte)

Zum scheinbar mühelosen Wechsel zwischen Welten. Hürden im Erwerb von Differenzkompetenz aus interfachdidaktischer Perspektive - Reis, Oliver; Kempfer, Karin; Hußmann, Stephan; Gärtner, Claudia (ÖRF)

Wie sehen sprachsensible Aufgabenstellungen für den Religionsunterricht aus? - Reis, Oliver; Lenze, Alina; Johanna, Nagels; Potthast, Fabian (Jahrbuch für Religionspädagogik)

Ethische Bildung im Religionsunterricht konstruktivistisch analysieren und ermöglichen - Reis, Oliver (Handbuch ethische Bildung. Religionspädagogische Fokussierungen)

Art. ‚Inklusion‘ - Reis, Oliver (Handbuch Religionsdidaktik)

Eingeprägte Ordnungen in digital gestützten Praktiken im (Religions-)Unterricht - Caruso, Carina; Reis, Oliver (Religion lernen. Jahrbuch für Konstruktivismus)

Struktur und Charisma in Zeiten von Corona. Leitbild – Modellprojekt – Evaluationsstudie. Lern- und Forschungsort - Reis, Oliver; Kolk, Matthias; Burke, Rebekka; Hackstedt, Carola; Hofmeister, Lisa; Rakowski, Jana (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Der PGR ohne amtliches Mitglied als Impuls für ein neues Rollengefüge - Hofmeister, Lisa; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Digitale und digital gestützte Lehre als Verstärker der Verunterrichtlichung von Hochschullehre? - Reis, Oliver (Forschungsimpulse für die Hochschulentwicklung im Kontext hybrider Lehre)

Was leisten modellgeleitete Interventionen für die Kirchenentwicklung? - Reis, Oliver; Kolk, Matthias; Burke, Rebekka; Hackstedt, Carola; Hofmeister, Lisa; Rakowski, Jana (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Die Corona-Pandemie als Stresstest der Strukturinterventionen - Burke, Rebekka; Hackstedt, Carola; Hofmeister, Lisa; Reis, Oliver (Projektbericht 1: Modelle, Transformationen, Corona-Erfahrungen)

Opportunities and Possibilities of a Network of Mathematical Learning and Support Centres in Germany - Schürmann, Mirko; Liebendörfer, Michael; Gildehaus, Lara; Schaper, Niclas; Hochmuth, Reinhard; Biehler, Rolf; Lankeit, Elisa; Kuklinski, Christiane; Ruge, Johanna (Sigma newsletter)

Was ist eine gute Skizze? Strategiewissen beim mathematischen Modellieren im Bereich der Geometrie fördern - Schönherr, Johanna; Schukajlow, S.; Blomberg, J. (mathematik lehren)

Does strategic knowledge matter? Effects of strategic knowledge about drawing on students’ modeling competencies in the domain of geometry - Schönherr, Johanna; Schukajlow, S.; Blomberg, J.; Leopold, C. (Mathematical Thinking and Learning)

Do emotions and prior performance facilitate the use of the learner-generated drawing strategy? Effects of enjoyment, anxiety, and intramathematical performance on the use of the drawing strategy and modelling performance - Schönherr, Johanna; Blomberg, J.; Schukajlow, S.; Leopold, C. (Contemporary Educational Psychology)

A fuzzy weighted influence non-linear gauge system with application to advanced technology assessment at NASA - Tavana, Madjid; Mousavi, Hossein; Khalili Nasr, Arash; Mina, Hassan (Expert Systems with Applications)

An integrated data envelopment analysis and life cycle assessment method for performance measurement in green construction management - Tavana, Madjid; Izadikhah, Mohammad; Farzipoor Saen, Reza; Zare, Ramin (Environmental Science and Pollution Research)

An integrated fuzzy sustainable supplier evaluation and selection framework for green supply chains in reverse logistics - Tavana, Madjid; Shaabani, Akram; Santos-Arteaga, Francisco J.; Valaei, Naser (Environmental Science and Pollution Research)

An integrated fuzzy AHP- fuzzy MULTIMOORA model for supply chain risk-benefit assessment and supplier selection - Tavana, Madjid; Shaabani, Akram; Mansouri Mohammadabadi, Soleyman; Varzgani, Nilofar (International Journal of Systems Science: Operations & Logistics)

An epsilon-based data envelopment analysis approach for solving performance measurement problems with interval and ordinal dual-role factors - Ebrahimi, Bohlool; Tavana, Madjid; Kleine, Andreas; Dellnitz, Andreas (OR Spectrum)

An integrated group fuzzy best-worst method and combined compromise solution with Bonferroni functions for supplier selection in reverse supply chains - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Bonyani, Abbas (Cleaner Logistics and Supply Chain)

A location-inventory-routing model for green supply chains with low-carbon emissions under uncertainty - Tavana, Madjid; Tohidi, Hamid; Alimohammadi, Milad; Lesansalmasi, Reza (Environmental Science and Pollution Research)

A novel fuzzy multi-objective circular supplier selection and order allocation model for sustainable closed-loop supply chains - Khalili Nasr, Arash; Tavana, Madjid; Alavi, Behrouz; Mina, Hassan (Journal of Cleaner Production)

An integrated and comprehensive fuzzy multicriteria model for supplier selection in digital supply chains - Tavana, Madjid; Shaabani, Akram; Di Caprio, Debora; Amiri, Maghsoud (Sustainable Operations and Computers)

A note and new extensions on “interval efficiency measures in data envelopment analysis with imprecise data” - Ebrahimi, Bohlool; Tavana, Madjid; Charles, Vincent (Operational Research)

A grey-DEMATEL approach for analyzing factors critical to the implementation of reverse logistics in the pharmaceutical care process - de Campos, Elaine Aparecida Regiani; Tavana, Madjid; ten Caten, Carla Schwengber; Bouzon, Marina; de Paula, Istefani Carísio (Environmental Science and Pollution Research)

An integrated information fusion and grey multi-criteria decision-making framework for sustainable supplier selection - Aslani, Babak; Rabiee, Meysam; Tavana, Madjid (International Journal of Systems Science: Operations & Logistics)

A Systematic Review of Organizational Factors Impacting Cloud-based Technology Adoption Using Technology-Organization-Environment Framework - Al Hadwer, Ali; Tavana, Madjid; Gillis, Dan; Rezania, Davar (Internet of Things)

An inventory-location optimization model for equitable influenza vaccine distribution in developing countries during the COVID-19 pandemic - Rastegar, Mehdi; Tavana, Madjid; Meraj, Afshin; Mina, Hassan (Vaccine)

An Integrated Fuzzy Goal Programming—Theory of Constraints Model for Production Planning and Optimization - Zare, Habib; Kamali Saraji, Mahyar; Tavana, Madjid; Streimikiene, Dalia; Cavallaro, Fausto (Sustainability)

A common weights model for investigating efficiency-based leadership in the russian banking industry - Kazemi, Sajad; Tavana, Madjid; Toloo, Mehdi; Zenkevich, Nikolay A. (RAIRO - Operations Research)

A simulation–optimization model for solving flexible flow shop scheduling problems with rework and transportation - Gheisariha, Elmira; Tavana, Madjid; Jolai, Fariborz; Rabiee, Meysam (Mathematics and Computers in Simulation)

A joint chance-constrained data envelopment analysis model with random output data - Khanjani Shiraz, Rashed; Tavana, Madjid; Fukuyama, Hirofumi (Operational Research)

A Dynamic Decision Support System for Sustainable Supplier Selection in Circular Economy - Alavi, Behrouz; Tavana, Madjid; Mina, Hassan (Sustainable Production and Consumption)

An integrated quality and resilience engineering framework in healthcare with Z-number data envelopment analysis - Tavana, Madjid; Nazari-Shirkouhi, Salman; Farzaneh Kholghabad, Hamidreza (Health Care Management Science)

An integrated fuzzy framework for analyzing barriers to the implementation of continuous improvement in manufacturing - Tavana, Madjid; Shaabani, Akram; Valaei, Naser (International Journal of Quality & Reliability Management)

A fuzzy maturity-based method for lean supply chain management assessment - Soares, Gabriela Pereira; Tortorella, Guilherme; Bouzon, Marina; Tavana, Madjid (International Journal of Lean Six Sigma)

A robust cross-efficiency data envelopment analysis model with undesirable outputs - Tavana, Madjid; Toloo, Mehdi; Aghayi, Nazila; Arabmaldar, Aliasghar (Expert Systems with Applications)

Four research pathways for understanding the role of smart technologies in accounting - Mancini, Daniela; Lombardi, Rosa; Tavana, Madjid (Meditari Accountancy Research)

A new non-radial directional distance model for data envelopment analysis problems with negative and flexible measures - Tavana, Madjid; Izadikhah, Mohammad; Toloo, Mehdi; Roostaee, Razieh (Omega)

The Cologne Picture Naming Test for Language Mapping and Monitoring (CoNaT): An Open Set of 100 Black and White Object Drawings - Weiss Lucas, Carolin; Pieczewski, Julia; Kochs, Sophia; Nettekoven, Charlotte; Grefkes, Christian; Goldbrunner, Roland; Jonas, Kristina (Frontiers in Neurology)
Language assessment using a picture naming task crucially relies on the interpretation of the given verbal response by the rater. To avoid misinterpretations, a language-specific and linguistically controlled set of unambiguous, clearly identifiable and common object–word pairs is mandatory. We, here, set out to provide an open-source set of black and white object drawings, particularly suited for language mapping and monitoring, e.g., during awake brain tumour surgery or transcranial magnetic stimulation, in German language. A refined set of 100 black and white drawings was tested in two consecutive runs of randomised picture order and was analysed in respect of correct, prompt, and reliable object recognition and naming in a series of 132 healthy subjects between 18 and 84 years (median 25 years, 64% females) and a clinical pilot cohort of 10 brain tumour patients (median age 47 years, 80% males). The influence of important word- and subject-related factors on task performance and reliability was investigated. Overall, across both healthy subjects and patients, excellent correct object naming rates (97 vs. 96%) as well as high reliability coefficients (Goodman–Kruskal's gamma = 0.95 vs. 0.86) were found. However, the analysis of variance revealed a significant, overall negative effect of low word frequency ( p < 0.05) and high age ( p < 0.0001) on task performance whereas the effect of a low educational level was only evident for the subgroup of 72 or more years of age ( p < 0.05). Moreover, a small learning effect was observed across the two runs of the test ( p < 0.001). In summary, this study provides an overall robust and reliable picture naming tool, optimised for the clinical use to map and monitor language functions in patients. However, individual familiarisation before the clinical use remains advisable, especially for subjects that are comparatively prone to spontaneous picture naming errors such as older subjects of low educational level and patients with clinically apparent word finding difficulties.

Improving the efficacy and reliability of rTMS language mapping by increasing the stimulation frequency - Nettekoven, Charlotte; Pieczewski, Julia; Neuschmelting, Volker; Jonas, Kristina; Goldbrunner, Roland; Grefkes, Christian; Weiss Lucas, Carolin (Human Brain Mapping)
Abstract Repetitive TMS (rTMS) with a frequency of 5–10 Hz is widely used for language mapping. However, it may be accompanied by discomfort and is limited in the number and reliability of evoked language errors. We, here, systematically tested the influence of different stimulation frequencies (i.e., 10, 30, and 50 Hz) on tolerability, number, reliability, and cortical distribution of language errors aiming at improved language mapping. 15 right‐handed, healthy subjects (m = 8, median age: 29 yrs) were investigated in two sessions, separated by 2–5 days. In each session, 10, 30, and 50 Hz rTMS were applied over the left hemisphere in a randomized order during a picture naming task. Overall, 30 Hz rTMS evoked significantly more errors (20 ± 12%) compared to 50 Hz (12 ± 8%; p <.01), whereas error rates were comparable between 30/50 and 10 Hz (18 ± 11%). Across all conditions, a significantly higher error rate was found in Session 1 (19 ± 13%) compared to Session 2 (13 ± 7%, p <.05). The error rate was poorly reliable between sessions for 10 (intraclass correlation coefficient, ICC = .315) and 30 Hz (ICC = .427), whereas 50 Hz showed a moderate reliability (ICC = .597). Spatial reliability of language errors was low to moderate with a tendency toward increased reliability for higher frequencies, for example, within frontal regions. Compared to 10 Hz, both, 30 and 50 Hz were rated as less painful. Taken together, our data favor the use of rTMS‐protocols employing higher frequencies for evoking language errors reliably and with reduced discomfort, depending on the region of interest.

Confinement Effects for Efficient Macrocyclization Reactions with Supported Cationic Molybdenum Imido Alkylidene N-Heterocyclic Carbene Complexes - Ziegler, Felix; Kraus, Hamzeh; Benedikter, Mathis J.; Wang, Dongren; Bruckner, Johanna R.; Nowakowski, Michał; Weißer, Kilian; Solodenko, Helena; Schmitz, Guido; Bauer, Matthias; Hansen, Niels; Buchmeiser, Michael R. (ACS Catalysis)
For entropic reasons, the synthesis of macrocycles via olefin ring-closing metathesis (RCM) is impeded by competing acyclic diene metathesis (ADMET) oligomerization. With cationic molybdenum imido alkylidene N-heterocyclic carbene (NHC) complexes confined in tailored ordered mesoporous silica, RCM can be run with macrocyclization selectivities up to 98% and high substrate concentrations up to 0.1 M. Molecular dynamics simulations show that the high conversions are a direct result of the proximity between the surface-bound catalyst, proven by extended X-ray absorption spectroscopy, and the surface-located substrates. Back-diffusion of the macrocycles decreases with decreasing pore diameter of the silica and is responsible for the high macrocyclization efficiency. Also, Z-selectivity increases with decreasing pore diameter and increasing Tolman electronic parameter of the NHC. Running reactions at different concentrations allows for identifying the optimum substrate concentration for each material and substrate combination.
Keywords: Catalysis; General Chemistry

Rh(I)/(III)‐N‐Heterocyclic Carbene Complexes: Effect of Steric Confinement Upon Immobilization on Regio‐ and Stereoselectivity in the Hydrosilylation of Alkynes - Panyam, Pradeep K. R.; Atwi, Boshra; Ziegler, Felix; Frey, Wolfgang; Nowakowski, Michał; Bauer, Matthias; Buchmeiser, Michael R. (Chemistry – A European Journal)
Rh(I) NHC and Rh(III) Cp* NHC complexes (Cp*=pentamethylcyclopentadienyl, NHC=N-heterocyclic carbene=pyrid-2-ylimidazol-2-ylidene (Py−Im), thiophen-2-ylimidazol-2-ylidene) are presented. Selected catalysts were selectively immobilized inside the mesopores of SBA-15 with average pore diameters of 5.0 and 6.2 nm. Together with their homogenous progenitors, the immobilized catalysts were used in the hydrosilylation of terminal alkynes. For aromatic alkynes, both the neutral and cationic Rh(I) complexes showed excellent reactivity with exclusive formation of the β(E)-isomer. For aliphatic alkynes, however, selectivity of the Rh(I) complexes was low. By contrast, the neutral and cationic Rh(III) Cp* NHC complexes proved to be highly regio- and stereoselective catalysts, allowing for the formation of the thermodynamically less stable β-(Z)-vinylsilane isomers at room temperature. Notably, the SBA-15 immobilized Rh(I) catalysts, in which the pore walls provide an additional confinement, showed excellent β-(Z)-selectivity in the hydrosilylation of aliphatic alkynes, too. Also, in the case of 4-aminophenylacetylene, selective formation of the β(Z)-isomer was observed with a neutral SBA-15 supported Rh(III) Cp* NHC complex but not with its homogenous counterpart. These are the first examples of high β(Z)-selectivity in the hydrosilylation of alkynes by confinement generated upon immobilization inside mesoporous silica.
Keywords: General Chemistry; Catalysis; Organic Chemistry

Immobilized Platinum Hydride Species as Catalysts for Olefin Isomerizations and Enyne Cycloisomerizations - Maier, Sarah; Cronin, Steve P.; Vu Dinh, Manh-Anh; Li, Zheng; Dyballa, Michael; Nowakowski, Michał; Bauer, Matthias; Estes, Deven P. (Organometallics)
Platinum hydride species catalyze a number of interesting organic reactions. However, their reactions typically involve the use of high loadings of noble metal and are difficult to recycle, making them somewhat unsustainable. We have synthesized surface-immobilized Pt–H species via oxidative addition of surface OH groups to Pt(PtBu3)2 (1), a rarely used immobilization technique in surface organometallic chemistry. The hydride species thus made were characterized by infrared, magic-angle spinning nuclear magnetic resonance, and X-ray absorption spectroscopies and catalyzed both olefin isomerization and cycloisomerization of a 1,6 enyne (5) with a high selectivity and low Pt loading.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry

Fundamental Characterization, Photophysics and Photocatalysis of a Base Metal Iron(II)‐Cobalt(III) Dyad - Huber-Gedert, Marina; Nowakowski, Michał; Kertmen, Ahmet; Burkhardt, Lukas; Lindner, Natalia; Schoch, Roland; Herbst‐Irmer, Regine; Neuba, Adam; Schmitz, Lennart; Choi, Tae‐Kyu; Kubicki, Jacek; Gawelda, Wojciech; et al. (Chemistry – A European Journal)
Keywords: Photocatalytic Hydrogen Production; Catalysis; Inorganic Chemistry

Work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and their impact on cultural participation - Flath, Beate; Momen Pour Tafreshi, Maryam (Arts and the Market)
Purpose The purpose of this article is to illuminate the relations of work-related practices of local managers of live music events in Ostwestfalen-Lippe (OWL) and barriers and needs of vulnerable customers (VC) in order to explore possibilities to increase cultural participation of VC. Design/methodology/approach This article explores work-related practices of managers of live music events in OWL and asks if and to what extent these practices have an influence on the cultural participation of “vulnerable customers” (VC). It combines the findings of two studies: a) an explorative investigation on the work-related self-conceptions of managers of live music events in OWL (Study 1), and b) a sub-project on cultural participation of VC, which is part of the research project “kulturPreis. Increasing cultural participation through innovative and economically sustainable pricing concepts”, funded by the German Federal Ministry of Education and Research (Study 2). Findings It can be stated that there is an imbalance of knowledge: while VC tend to have a clear understanding of which barriers are the responsibility of managers of live music events, managers tend to lack knowledge regarding the needs of VC, and regarding the interrelationships between financial and social barriers facing them. Whether this knowledge and understanding can be developed in the future depends on the possibilities of exchanges between managers of live music events, cultural institutions, welfare organisations, political institutions and not least VC. Originality/value Based on these studies, this article combines different approaches by linking work-related practices of managers of live music events with cultural participation of VC.

Digitale Stille. Über die Bedeutung von Universitäten und Wissenschaft in der Covid-19-Pandemie - Flath, Beate (Das HEFT. Das Paderborner Veranstaltungs- und Kulturmagazin)

Data-Based Co-Creation and Participation: Reflections on an Ambivalent Relation by the Example of Music Apps - Flath, Beate (Pop – Power – Positions. Globale Beziehungen und populäre Musik (~Vibes – The IASPM D-A-CH Series 1)

Das Besondere und das Allgemeine in musikdidaktischen Kontexten. - Klingmann, Heinrich (Musikalische Bildung. Didaktik - Lehrerinnen- und Lehrerbildung - Theorie. Festschrift für Werner Jank.)

Doing Popkultur. - Klingmann, Heinrich; Ahlers, Michael (Musik-Didaktik. Praxishandbuch für die Sekundarstufe 1 und 2)

Textsortengeschichte - Markewitz, Friedrich (WSK Band 6 (Wörterbücher zur Sprach- und Kommunikationswissenschaft): Text- und Diskurslinguistik)

Das „geheime Europa“. Hugo von Hofmannsthals späte Parallelaktion zu Stefan Georges „geheimem Deutschland“ (1919–1923) - Heise, Tillmann („Sehnsucht nach dem Leben“. Tradition und Innovation im Werk Hugo von Hofmannsthals)

Das ‚Erfundene Gespräch‘ als transatlantischer Dialog. Gattungsvariationen und Gedankenexperimente in Hofmannsthals Gesprächsfragment "Brief ans Dial" (1925) - Heise, Tillmann (Hofmannsthal-Jahrbuch)

Verfreundete Europäer im Kampf mit der Moderne - Heise, Tillmann; Beßlich, Barbara (Ruperto Carola Forschungsmagazin)

A mathematical programming approach for equitable COVID-19 vaccine distribution in developing countries - Tavana, Madjid; Govindan, Kannan; Nasr, Arash Khalili; Heidary, Mohammad Saeed; Mina, Hassan (Annals of Operations Research)

Kriterien der Sanktionierung einer Verletzung der Bonitätsprüfungspflicht - Bartlitz, David (Neue Juristische Wochenschrift (NJW))

Zum Anscheinsbeweis bei der Verwendung von Zahlungskarten mit PIN und zur Pflicht zur Sperranzeige. Anmerkung zu OLG Bremen, Beschl. v. 19.05.2021 - 1 W 4/21 - Bartlitz, David (Entscheidungen zum Wirtschaftsrecht (EWiR))

Ärger vor der Registereintragung - Bartlitz, David (Juristische Arbeitsblätter (JA))

Kooperatives Lernen von Lehramtsstudierenden im Zusammenhang mit ihrer Qualifizierung für den inklusiven naturwissenschaftlichen Sachunterricht der Grundschule – Schlussfolgerungen und Implikationen. Vortrag. Abschlussveranstaltung der Förderlinie "Qualifizierung der pädagogischen Fachkräfte für inklusive Bildung" des Bundesministeriums für Bildung und Forschung (BMBF) - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne

Melina Mercouri "Ich bin Griechin" (Είμαι Ρωμιά) - Janus, Richard (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Musik als Lebensmittel - Janus, Richard; Keuchen, Marion (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Themenpredigt: Reformation mit Beuys feiern - Janus, Richard (Reformation mit Joseph Beuys feiern. 31. Oktober 2021)

Reformation mit Joseph Beuys feiern. 31. Oktober 2021

Zeichen der Gemeinschaft und Begegnung. Göttliche Dreieinigkeit in der Orthodoxie - Janus, Richard

Dritte Internationale Summer School: "Formation of Faith and Trust" - Janus, Richard

Beeinflussung der Fließeigenschaften von Lasersinterpulver mittels Fließhilfsmitteln - Man, Yunhao

Wärmebehandlung von Polymeren zum Modifizieren von Materialeigenschaften für das Selektive Lasersintern - Seuthe, Jan

Fließfähigkeit von Schüttgütern bei erhöhten Temperaturen (Studienarbeit) - Ewe, Frederik

Untersuchung der mechanischen und geometrischen Eigenschaften von Bauteilen hergestellt im Fused Deposition Modeling Verfahren - Knoop, Frederick
Im Rahmen dieser Arbeit wird das additive Fertigungsverfahren Fused Deposition Modeling (FDM) hinsichtlich der erzielbaren Bauteilqualität untersucht. Der Fokus liegt auf den mechanischen und geometrischen Eigenschaften für Bauteile aus ABS-M30. Hierzu erfolgt eine grundlegende Eruierung aller Einflussfaktoren auf die Bauteilqualität. Die Einflussfaktoren, die von besonderer Bedeutung sind, werden mithilfe von experimentellen Untersuchungen genauer analysiert. Ein wichtiges Merkmal im FDM-Prozess ist die Temperatur und die Luftströmung im Bauraum der Fertigungsmaschine, sodass neben der Ermittlung des Istzustandes auch eine Optimierung dieser erarbeitet wird. In den weiteren Hauptkapiteln wird neben dem Einfluss der Temperatur und Luftströmung auch der Einfluss der Strangablagestrategie untersucht. Die Strangablagestrategie kann zu einer gezielten Verbesserung der mechanischen Eigenschaften von FDM-Bauteilen genutzt werden. Die Einflüsse der Strangablagestrategie auf die geometrischen Bauteileigenschaften werden in Form von Maß- und Formabweichungen ermittelt. Ein weiteres Ziel dieser Arbeit ist die grundlegende Analyse über die Ursache von Maßabweichungen an FDM-Probekörpern. Zur Reduzierung der auftretenden Maßabweichungen, wird eine Methode erarbeitet, die zur Bestimmung von optimierten Schwindungsfaktoren dient. Die optimierten Schwindungsfaktoren werden genutzt, um die Maßabweichungen an FDM-Bauteilen maßgeblich zu reduzieren.

Oberflächennachbehandlung beim Fused Deposition Modeling – Analyse der Oberflächenstruktur und mechanischer Kennwerte - Fischer, Matthias
Mit seiner Eignung für den Einsatz in Luftfahrzeugen stellt vor allem der Werkstoff Ultem 9085 in Verbindung mit der Verarbeitbarkeit im Fused Deposition Modeling (FDM) Prozesses ein großes Potential für die Kleinserienfertigung mittels additiver Fertigungstechnologien im Luftfahrtbereich dar. Hier bestehen aufgrund der Schichtbauweise Herausforderungen zur Optimierung der Oberflächenqualität. Des Weiteren ist das Ermüdungsverhalten von FDM-Strukturen noch unzureichend erforscht. Mit dem Schwerpunkt auf dem Werkstoff Ultem 9085 sind im Rahmen dieser Dissertation zunächst Nachbehandlungsmethoden zur Verbesserung der Oberflächenqualität analysiert worden. Hier konnten Oberflächenrauheiten durch den Einsatz eines chemischen Nachbehandlungsprozesses um bis zu 80 % reduziert werden. Die dabei als Nebeneffekt erzeugte Schließung der porösen Oberflächenstruktur begünstigte zudem einen anschließenden Metallisierungsprozess zur Veredelung der Oberflächenstruktur. Die Ermüdungseigenschaften fallen für FDM-Strukturen aufgrund der inneren und äußeren Kerben im Vergleich zu spritzgegossenen Substraten vergleichsweise gering aus. Durch Überfüllung der Bau-teile und gezielte Strangorientierungen kann die Lebensdauer insbesondere für seitlich und flach aufgebaute Zugprüfkörper erhöht werden. Der chemische Nachbehandlungsprozess wirkt sich durch die Reduzierung von äußeren Kerben vor allem positiv auf die mechanischen Eigenschaften von aufrecht hergestellten Strukturen aus.

Beyond words: Children’s multimodal responses during word learning with a social robot - Tolksdorf, Nils Frederik; Mertens, Ulrich J. (International Perspectives on Digital Media and Early Literacy)
Digital devices such as social robots are increasingly being developed as artificially intelligent learning tools that could support and expand early childhood education by providing new ways to engage children in social interaction. Given this potential, research in child-robot interaction has begun to investigate which aspects of a robot’s behavior provide advantages within the interaction. However, a perspective that addresses the child’s communicative behavior within a child-robot interaction is seldom explored. In this chapter, the results of a long-term child-robot study with preschool children are presented, in which children’s multimodal response behavior during a word learning task with a social robot was in focus. The results reveal that children not only used different communicative multimodal signals such as gestures or delay markers when interacting with the robot, but also changed their behavior over the course of the sessions. The findings suggest that children shape their responses to a robot in a manifold multimodal way beyond verbal lexical utterances. Finally, implications for future child-robot interaction research, as well as identifying issues that will need to be resolved for social robots to be helpful and responsive in interaction with young learners, are discussed.

Forcierte Form

Additive Leichtbaustrukturen für die Flugzeugkabine - Menge, Dennis; Klippstein, Sven Helge; Schmid, Hans-Joachim

Kompetenzförderung im Laborpraktikum - Sacher, Marc; Bauer, Anna (Labore in der Hochschullehre. Didaktik, Digitalisierung, Organisation)

Studentische Akzeptanz und Relevanzwahrnehmung eines disziplinspezifischen Workshops „Wissenschaftliche Vorträge in der Physik“ - Bauer, Anna; Sacher, Marc; Brassat, Katharina (hochschullehre)

Entwicklung eines Bewertungsmodells zur handlungsorientierten Messung experimenteller Kompetenz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Phydid B, Didaktik der Physik, Beiträge zur DPG-Frühjahrstagung)

Bewertungsmodell zur experimentellen Performanz (Physik)Studierender - Bauer, Anna; Reinhold, Peter; Sacher, Marc (Naturwissenschaftliche Kompetenzen in der Gesellschaft von morgen)

Überlegungen auf dem Weg zu einer Theorie lehrbezogenen Wandels an Hochschulen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Die Frage, wie sich die Weiterentwicklung der Lehre an Hochschulen systematisch verankern lässt, erfährt mit dem Auslaufen von Förderprogrammen wie dem QPL erneute Aufmerksamkeit. Bislang fehlt es an einer kontextspezifischen Theorie, die lehrbezogenen Wandel an Hochschulen analysier- und gestaltbar macht. In jedem Fall sind Change-Konzepte aus dem betriebswirtschaftlichen Bereich nur sehr beschränkt auf Hochschulen übertragbar. Demgegenüber gibt neuere Forschung Hinweise darauf, welche Kernkategorien eine hochschulspezifische Change- Theorie umfassen könnte. Darauf aufbauend schlägt der Beitrag zwei Konzepte als Kernkategorien einer Theorie lehrbezogenen Wandels an Hochschulen vor.
Keywords: educational development; change management; educational innovation

Analytical characterization of polyamide 11 used in the context of selective laser sintering: Physico-chemical correlations - Scherer, Beate; Kottenstedde, Ingo Leonard; Bremser, Wolfgang; Matysik, Frank-Michael (Polymer Testing)

HOBBIT: A platform for benchmarking Big Linked Data - Röder, Michael; Kuchelev, Denis; Ngonga Ngomo, Axel-Cyrille (Data Sci.)

Squirrel - Crawling RDF Knowledge Graphs on the Web - Röder, Michael; de Souza, Geraldo; Ngonga Ngomo, Axel-Cyrille (The Semantic Web - ISWC 2020 - 19th International Semantic Web Conference, Athens, Greece, November 2-6, 2020, Proceedings, Part II)

Applying edge-counting semantic similarities to link discovery: scalability and accuracy - Georgala, Kleanthi; Ahmed Sherif, Mohamed; Röder, Michael; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 15th International Workshop on Ontology Matching co-located with the 19th International Semantic Web Conference {(ISWC} 2020), Virtual conference (originally planned to be in Athens, Greece), November 2, 2020)

Analysis of DTLS Implementations Using Protocol State Fuzzing - Fiterau-Brostean, Paul; Jonsson, Bengt; Merget, Robert; de Ruiter, Joeri; Sagonas, Konstantinos; Somorovsky, Juraj (29th USENIX Security Symposium (USENIX Security 20))

LIGON - link discovery with noisy oracles - Ahmed Sherif, Mohamed; Dreßler, Kevin; Ngonga Ngomo, Axel-Cyrille (Proceedings of the 15th International Workshop on Ontology Matching co-located with the 19th International Semantic Web Conference {(ISWC} 2020), Virtual conference (originally planned to be in Athens, Greece), November 2, 2020)